2017
DOI: 10.19080/gjarm.2017.01.555562
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic properties and metal analysis of Bombax ceiba flower extracts

Abstract: The plant may be considered a bio-synthetic laboratory, not only for the bio-chemicals such as carbohydrates, protein, and lipid that are utilized as food by man, but also for a multitude of compounds like glycosides, alkaloids, tannins etc, that exerts physiological effects. The compound those are responsible for therapeutic effects are usually the secondary metabolite. Bombex ceiba plant extracts have been evaluated for its antidiabetic properties by in-vitro inhabitation of alpha amylase and alpha glucosida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…This also proved that α-glucosidase inhibitory activity was the combined effect of various bioactive substances in BCF. Previous studies have reported the hypoglycemic activity of BCF in vitro and in vivo ( 36 , 37 ), which was in accordance with our experimental results. Given that the in vivo hypoglycemic activity of the n-BuOH and EtOAc fractions merit further investigation.…”
Section: Resultssupporting
confidence: 93%
“…This also proved that α-glucosidase inhibitory activity was the combined effect of various bioactive substances in BCF. Previous studies have reported the hypoglycemic activity of BCF in vitro and in vivo ( 36 , 37 ), which was in accordance with our experimental results. Given that the in vivo hypoglycemic activity of the n-BuOH and EtOAc fractions merit further investigation.…”
Section: Resultssupporting
confidence: 93%
“…The Phytochemical compositions of methanol extract of the Egyptian B. ceiba flowers indicate the presence of alkaloids, flavonoids, glycosides, saponine, polyphenols, tannins, proteins, carbohydrates, lipids, amino acids and coumarins [33,34]. These valuable compounds offer the potent antioxidant and hypolipedimic properties of BCE in the liver tissues [35].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to consider metabolic pathways as groups of metabolites that share a common biological process and are related by one or more enzymatic reactions. A broad set of metabolic pathways are covered by comprehensive metabolic pathway databases, such as the KEGG database [173], MetaCyc [174], AraCyc [175] and the small molecule pathway database (SMPDB) [176] (Table 5). A number of software, such as, metabolite set enrichment analysis (MSEA), MPEA, IMPaLA, MBRole, VANTED, Metabo-Analyst, Paintomics, ProMeTra, Metscape2, and MetaMapRR can perform statistical and other metabolite enrichment analyses (Table 5).…”
Section: Network Analysismentioning
confidence: 99%
“…Bombax ceiba L. The dichloromethane, ethanol, and aqueous thalamus and flower extracts of B. ceiba were reported for their antidiabetic properties in terms of their capacity to inhibit alpha-amylase and alpha-glucosidase enzymes under in vitro condition. The corresponding IC 50 values for alpha-amylase inhibition activities for thalamus were 36.22 µg/mL (dichloromethane extract), 35.32 µg/mL (ethanolic extract), and 31.31 µg/mL (aqueous extract) and for flowers, 38.13 µg/mL (dichloromethane extract), 35.23 µg/mL (ethanolic extract), and 33.00 µg/mL (aqueous extract) [174]. The n-hexane fraction of sepals [175] and ethanolic leaf extracts [177] of B. ceiba exhibited antidiabetic activities in STZ-induced diabetic rats.…”
Section: Conflicts Of Interestmentioning
confidence: 99%